A scoping review linking early childhood caries to violence, neglect, internally displaced, migrant and refugee status - Morenike Oluwatoyin Folayan; Robert J. Schroth; Imen Ayouni; Arthemon Nguweneza; Arheiam Arheiam; Ola B. Al-Batayneh; Jorma I. Virtanen; Balgis Gaffar; Duangporn Duangthip; Ivy Guofang Sun; Simin Mohebbi; Carlos A. Feldens; et al. (BMC, 2023)
Abstract Background The aim of the scoping review was to identify and synthesize the available literature concerning the relationship between the status of refugees, migrants, and internally displaced persons (IDPs) and Early Childhood Caries (ECC) as it relates to the United Nation's Sustainable Development Goal 16 (SDG 16). Methods Data regarding the links between the status of refugees, migrants, and internally displaced persons (IDPs) and Early Childhood Caries (ECC), and the associations between ECC and maternal and child exposure to physical and sexual abuse, insecurity, crime, exploitation, torture, and displacement were extracted. The search was carried out in January 2023 across three databases (PubMed, Web of Science, and Scopus). Only publications in English with accessible full texts were included. Descriptive statistics were utilized to summarize the categories of the retrieved papers, and graphical representation was employed for visualization purposes. The relationships between the publications and each of the 10 targets of Sustainable Development Goal 16 (SDG 16) were also assessed. Results Forty-five studies were reviewed. Most studies (42.2%) originated from the Americas Regions, while no studies were identified from the Africa Region. A significant portion (46.7%) of the papers focused on abuse, violence, and neglect as risk factors for ECC. Migrants, refugees, and IDPs were the most investigated populations (44.4%). Only one study specifically focused on IDPs and migrants respectively. The prevalence of untreated caries was higher among migrants, refugees, and IDPs compared to the host community, ECC was more prevalent among children who experienced abuse, neglect, or were in protective care. The was no clear direction on the associations between ECC and intimate partner violence, adverse childhood experiences, and wars. In terms of the SDGs, the reviewed publications addressed four targets (SDG16.1, SDG16.2, SDG16.3, and SDG16.5) out of the ten targets outlined in SDG 16. Conclusion There is available evidence regarding the connections between ECC and war, refugees, migration, violence, and neglect, as outlined in SDG 16. Future studies are needed to investigate how forced movements directly affects ECC status, how disruptions of peace and stability is a risk factor for ECC, and the associations between ECC and other indicators related to SDG 16 targets.